READING HABITS AND PREFERENCES OF EFL POST GRADUATES: A CASE STUDY - Mohd. Noor, Noorizah (Universitas Pendidikan Indonesia, 2011)
In recent years, more emphasis has been given on the role of the learner in the language learning process considering that language learning is primarily a learner’s oriented activity. Thus, learners’ needs and interests should be taken into consideration for effective language learning and teaching to take place. One significant area where learners’ preferences influence their learning can be seen in reading. In any academic or higher learning context, reading is perceived as the most prominent academic language skill for all second and foreign language learners. It is through reading that these learners learn new information and become able to synthesize, evaluate and interpret in order to learn more about their subject matter. Pursuing a postgraduate study requires extensive reading practices which will enable the learners to extend their literacy development. The present study examines the reading habits and preferences of a group of EFL graduate students. Data was collected through a questionnaire and analysed quantitatively. The findings will report on: i) the types of reading materials preferred ii) reasons for reading and iii) the preferred language for reading. To conclude, the paper will further discuss the implications of the findings in terms of instructional materials development within an EFL context. Key words: EFL learners, reading habits, reading preferences, reading behaviour